Analysis of Companies' Adaptive Strategies in Facing Global Economic Uncertainty - Yogi Priambada; Dwi Utami Puterisari (Oikonomia : Journal of Management Economics and Accounting, 2025)
Global economic uncertainty characterized by macroeconomic volatility, geopolitical fragmentation, supply chain disruptions, and rapid digital transformation demands that firms adopt more integrated adaptive strategies. This study aims to analyze corporate adaptive strategies in responding to global uncertainty using a Systematic Literature Review (SLR) approach. The SLR process involved identification, screening, eligibility assessment, and thematic analysis of 24 relevant peer-reviewed publications from the last decade. The findings indicate that dynamic capabilities, digital transformation, and organizational flexibility form the core foundation of effective adaptive strategies. Sensing, seizing, and reconfiguring capabilities strengthen organizational resilience, while digital technologies enhance decision-making speed, operational efficiency, and strategic innovation. Organizational flexibility further enables rapid responses to environmental changes through decentralized and collaborative structures. This study concludes that adaptive strategies should be designed as an integrated model comprising organizational resilience, strategic innovation, and fast adaptive responses, supported by public policies that strengthen the adaptive ecosystem of firms in developing economies.